A high-fat diet fed during different periods of life impairs steroidogenesis of rat Leydig cells. Issue 6 (December 2016) - Pinto-Fochi, Maria Etelvina; Pytlowanciv, Eloísa Zanin; Reame, Vanessa; Rafacho, Alex; Ribeiro, Daniele Lisboa; Taboga, Sebastião Roberto; Góes, Rejane Maira
Abstract : This study evaluated the impact of a high-fat diet (HFD) during different stages of rat life, associated or not with maternal obesity, on the content of sex steroid hormones and morphophysiology of Leydig cells. The following periods of development were examined: gestation (O1), gestation and lactation (O2), from weaning to adulthood (O3), from lactation to adulthood (O4), gestation to adulthood (O5), and after sexual maturation (O6). The HFD contained 20% unsaturated fat, whereas the control diet had 4% fat. Maternal obesity was induced by feeding HFD 15 weeks before mating. All HFD groups presented increased body weight, hyperinsulinemia and reduced insulin sensitivity. Except for O1, all HFD groups exhibited a higher adiposity index, hyperleptinemia, reduced testosterone and estradiol testicular levels, and decreased testicular 17β-HSD enzyme . Morphometrical analyses indicated atrophy of Leydig cells in the O2 group. Myelin vesicles were observed in the mitochondrial matrix of Leydig cells in O3, O4, O5 and O6, and autophagosomes containing mitochondria were found in O5 and O6. In conclusion, HFD feeding, before or after sexual maturation, reduces the functional capacity of rat Leydig cells. Maternal obesity associated with HFD during pregnancy/lactation prejudices Leydig cell steroidogenesis and induces its atrophy in adulthood, even if it is replaced by a conventional diet at later stages of life. Regardless of the life period of exposure to HFD, deregulation of leptin is the main factor related to steroidogenic impairment of Leydig cells, and, in groups exposed for longer periods (O3, O4, O5 and O6), this is worsened by structural damage and mitochondrial degeneration of these cells.